Clinical-anamnestic features and quality of life in women with endometrial pathology on the background of uterine myoma. - Dronova, V. L.; Kornienko, S. M. (Medicni Perspektivi, 2017)
A total of 325 women 35-55 years old suffering from various forms of endometrial pathology were examined. It was found that 110 (33.8%) patients had combination of endometrial pathology and uterine myoma. They made up the main group (group MM), the reference group consisted of 215 women without uterine myoma (group K). It was established that group with uterine myoma is characterized by increased extragenital morbidity: cardiomyopathy (p<0.009), hypertension (p<0.03), obesity stage III-IV (p<0.006), iron-deficiency anemia (p<0,02), vegetative-vascular dystonia (p<0,03) and nervous system diseases (p<0,01) were significantly more common. The presence of uterine myoma is associated with increased risk of recurrence of endometrial hyperplasia and polyps. These data suggest that in the pathophysiology of uterine myoma in women of late reproductive and premenopausal age with endometrial pathology somatic and somatoform disorders play a more significant role than concomitant or previous genital pathology. In late reproductive age and menopause period endometrial lesions are combined with uterine myoma in every third patient. Somatic factors have a greater impact on the development of uterine myoma than reproductive. The presence of uterine myoma is an additional criterion of reduceof quality of life and burdens the prognosis of treatment of endometrial pathology in late reproductive age and premenopausal period.